Internal Audit Evaluation at the National Zakat Agency of Banjarmasin City Based on the Latest Decision - Fadhillah, Rizky; Nadiah; Sadewa, Manik Mutiara (Sinergi International Journal of Accounting and Taxation, 2025)
Effective zakat fund management requires transparent and accountable governance. Internal audits play a crucial role in ensuring public trust and operational efficiency in zakat management organisations such as the National Zakat Agency of Banjarmasin City. This study aims to evaluate the implementation of internal audits at the National Zakat Management Agency of Banjarmasin City, with a specific focus on compliance with the recently issued National Zakat Management Agency Decisions No. 98 and 99 of 2024. Using a descriptive qualitative approach, this research collected data through questionnaires and interviews with 13 key informants, including leaders, internal auditors, and auditees. The results of this study indicate that, although the National Zakat Agency of Banjarmasin City has a strong formal internal audit structure, its practical implementation requires strengthening at all stages of planning, implementation, and follow-up. The main challenges identified include a lack of trust from operational units, the absence of a clear formal audit mandate, limited access to information, and difficulties in fully integrating audit practices into the organisational culture. Additionally, coordination issues in follow-up actions were also identified. However, the overall process of planning, establishing, implementing, evaluating, reporting, and following up on internal audits generally scored well (average 4.3–4.7 out of 5), indicating a positive foundation for the organisation.